Sistem Pengepakan Botol Minuman Kemasan Berbasis Programmable Logic Controller - Samuel Y. Dimpudus; Vecky C. Poekoel; Pinrolinvic D.K. Manembu (Universitas Sam Ratulangi, 2015)
Abstract - The sophistication of machines in the global world today has grown rapidly. The increasing human needs also spur its development. In order to facilitate human life that formerly cooking water for their drink, at this time water is packaged in bottles to be consumed anywhere. Therefore, factory of qualified bottled water is highly demanded to meet the health needs of consumers. Most plants already have automated tools ranging from raw material to finishing product, but there are also plants that do not have one of these technologies included in North Sulawesi. Then the technology developer in North Sulawesi, especially colleges is need to try to develop these technologies, including the packing section which is still using manpower. Design and manufacture of packing system's prototype for bottled water (more specifically the packaging for 600ml) with good mechanical parameters and good software will support these packing process. Using Electricity even air (pneumatic) in the system manufacture was performed. For controlling system, there used PLC (Programmable Logic Controllers) Siemens S7-300 CPU 314C-2 DP. Mechanical systems use materials armed with iron and aluminum with propulsion of direct current electric motors and pneumatic cylinders. Based on the size of the bottle and carton, frame and mechanical systems are made. Maximum average current of 12V DC motor is for lifting weights with 2,036 A, and on a 24 V DC motor is for right motion (with load) with 0.184 A. The force generated from pneumatic cylinder with 2 bar pressure for clasping load is 40.192 N while at the starting position/ release the load is 36.267 N. The total volume of air compression required for cylinder is 0.1415512 liters. From the test results, it was concluded that the system can work well although with a slightly longer time. It is hoped that an air vacuum system can be used in the future development to facilitate packing bottles of bottled water. Keywords: bottles, force, motor, packing, PLC, pneumatic, time, volume Abstrak - Kecanggihan mesin di dunia global sekarang ini telah berkembang dengan sangat pesat. Semakin bertambahnya kebutuhan manusia pun memacu perkembangan hal itu. Demi mempermudah kehidupannya pun manusia yang pada awalnya memasak air minum pada saat ini mengemasnya dalam botol untuk dapat dikonsumsi dimana saja. Karena itu, pabrik air minum kemasan yang berkualitas sangat dituntut untuk memenuhi kebutuhan kesehatan konsumen. Kebanyakan pabrik telah memiliki alat otomatis mulai dari bahan mentah sampai produk jadi, tetapi ada juga pabrik yang belum memiliki teknologi tersebut salah satunya di Sulawesi Utara. Maka pengembang teknologi di Sulawesi Utara terutama pendidikan tinggi yang ada harus berusaha mengembangkan teknologi tersebut, termasuk pada bagian pengepakan yang masih menggunakan tenaga manusia. Perancangan dan pembuatan prototipe sistem pengepakan botol air minum dalam kemasan (lebih khusus kemasan 600mL) dengan parameter mekanik dan program yang baik akan menunjang proses pengepakan yang dimaksud. Penggunaan listrik bahkan udara (pneumatik) dalam pembuatan sistem pun dilakukan. Untuk pengontrolan sistem, digunakan PLC (Programmable Logic Controller) Siemens S7-300 CPU 314C-2 DP. Mekanik sistem menggunakan bahan besi dan aluminium berbekal penggerak berupa motor listrik arus searah dan silinder pneumatik. Berdasarkan pada ukuran botol dan karton, rangka dan mekanik sistem dibuat. Arus rata-rata maksimum pada motor DC 12V adalah pada saat mengangkat beban yaitu 2,036 A, dan pada motor DC 24 V adalah pada saat gerak ke kanan (dengan beban) yaitu 0,184 A. Gaya yang dihasilkan silinder pneumatik pada saat menjepit beban dengan tekanan 2 bar adalah sedangkan pada saat posisi awal/melepas beban adalah . Jumlah volume kompresi angin yang dibutuhkan silinder adalah 0,1415512 liter. Dari hasil pengujian, disimpulkan bahwa sistem dapat bekerja dengan baik walaupun dengan waktu yang sedikit lama. Dengan begitu, diharapkan bahwa alat sistem vakum udara dapat digunakan ke depannya untuk mempermudah pengepakan botol air minum dalam kemasan. Kata kunci: botol, gaya, motor, pengepakan, , PLC, pneumatic, volume, waktu